Surgical Management of Carney Complex‐Associated Pituitary Pathology. Issue 5 (May 2017) - Lonser, Russell R.; Mehta, Gautam U.; Kindzelski, Bogdan A.; Ray‐Chaudhury, Abhik; Vortmeyer, Alexander O.; Dickerman, Robert; Oldfield, Edward H.
Abstract : BACKGROUND: : Carney complex (CNC) is a familial neoplasia syndrome that is associated with pituitary‐associated hypersecretion of growth hormone (GH) (acromegaly). The underlying cause of pituitary GH hypersecretion and its management have been incompletely defined. OBJECTIVE: : To provide biological insight into CNC‐associated pituitary pathology and improve management, we analyzed findings in CNC patients who underwent transsphenoidal surgery. METHODS: : Consecutive CNC patients at the National Institutes of Health with acromegaly and imaging evidence of a pituitary adenoma(s) who underwent transsphenoidal resection of tumor(s) were included. Prospectively acquired magnetic resonance imaging and biochemical, surgical, and histological data were analyzed. RESULTS: : Seven acromegalic CNC patients (2 male, 5 female) were included. The mean age at surgery was 29.7 years (range, 18‐44 years). The mean follow‐up was 4.7 years (range, 0.2‐129 months). Magnetic resonance imaging revealed a single pituitary adenoma in 4 patients and multiple pituitary adenomas in 3 patients. Whereas patients with single discrete pituitary adenomas underwent selective adenomectomy, patients with multiple adenomas underwent selective adenomectomy of multiple tumors, as well as partial or total hypophysectomy. All adenomas were either GH and prolactin positive or exclusively prolactin positive. Pituitary tissue surrounding the adenomas in patients with multiple adenomas revealed hyperplastic GH‐ and prolactin‐positive tissue. CONCLUSION: : CNC‐associated acromegaly results from variable pituitary pathology, including a single GH‐secreting adenoma or multiple GH‐secreting adenomas and/or GH hypersecretion of the pituitary gland surrounding multiple adenomas. Although selective adenomectomy is the preferred treatment for cases of GH‐secreting adenomas, multiple adenomas with associated pituitary gland GH hypersecretion may require partial or complete hypophysectomy to achieve biochemical remission.